Stateczność Pręta Opływanego Równoległym Strumieniem Płynu przy Uwzględnieniu Oporu Czołowego - Kordas, Z. (Engineering Transactions, 1965)
The above problem concerns a bar (plate) clamped at one end. The load is composed of a front drag and lateral load acting after the stability loss. The introduction contains a brief survey of the literature concerning the stability analysis of elements in a fluid flow. It is found that this problem has hitherto been treated in an incomplete manner the front load or the lateral load being the only considered. The present paper presents a tentative analysis of the stability problem of a bar under the combined the hydraulic forces being. The main stress is laid on the stability analysis, the magnitude of the determined on the grounds of the theory of plane sections (Eq. 2.1). Sec. 2 contains the assumptions and the derivation of the fundamental equation small lateral vibration of the bar (Eq. 2.5). Sec. 3 is concerned with accurate stability analysis of the equation obtained in cases where the static criterion is sufficient. The range where the kinetic criterion is necessary is considered in Sec. 4. where the energy method is used. In this section the equation of the limit curve is obtained for an assumed form of the deflection line in the applicability range ofthe static and kinetic stability criterion.Next, the equations obtained are analysed in detail by describing the form of the limit curves using as coordinates the dimensionless flow velocity v and the dimensionless front drag s (Figs. 8, 9). Fig. 11 shows the form of the limit curves for various values of the "follow-up" parameter n and Fig. 10 – for various values of the parameter θ, characterizing the influence of the convection velocity of flow.